Bright, but allergic and neurotic? A critical investigation of the “overexcitable genius” hypothesis - Fries, Jonathan; Baudson, Tanja Gabriele; Kovacs, Kristof; Pietschnig, Jakob (Frontiers in Psychology, 2022)
Introduction Higher intelligence has been associated with improved health and longevity. However, recent findings have claimed that exceptional intelligence may come at a cost. Individuals at the upmost end of the intelligence distribution are reported to be disproportionately afflicted by a set of stress-related physical and mental health conditions: so-called overexcitabilities. Few accounts have investigated this issue and no studies are available for non-US samples yet. Here, we aimed to replicate and extend previous work by examining hitherto unaddressed overexcitabilities in a European high-IQ sample. Methods We carried out a preregistered survey among members of MENSA, the world’s largest high-IQ society. In total, 615 (307 male) members from Austria, Germany, Hungary, Switzerland, and the United Kingdom participated. Results and Discussion Compared to the general population, our sample exhibited considerably elevated prevalences in autism spectrum disorders (risk ratio/RR = 2.25), chronic fatigue syndrome (RR = 5.69), depression (RR = 4.38), generalized anxiety (RR = 3.82), and irritable bowel syndrome (RR = 3.76). Contrary to previous accounts, neither asthma, allergies, nor autoimmune diseases were elevated. We show that this subsample of intellectually gifted persons faces specific health challenges compared to the general population. The reasons for this remain speculative, as we find little evidence for previously proposed immunological explanations. However, it is possible that the effects are caused by sample selectiveness (i.e., membership in a high-IQ society) rather than high IQ itself.